Large-scale experimental and simulation study on gas explosion venting load characteristics of urban shallow buried pipe trenches. (May 2022) - Yang, Ya; Yang, Shigang; Fang, Qin; Xiang, Hengbo; Sun, Wenshen; Liu, Xin
Highlights: The pressure–time history curve in pipe trench has a single peak with four stages. The overpressure reach maximum values at the methane concentration of 9.5 vol%. The vent leads to the sudden drop and jump of the pressure upstream and downstream. Adding vents effectively reduces the upstream overpressure and overall impulse. The impulse is attenuated to a greater degree than the overpressure. Abstract: In this study, a series of explosion venting tests on a large-scale test system (30 m length) and numerical simulations were conducted to evaluate the venting behavior and venting load of a gas explosion in an urban shallow buried pipe trench according to the methane concentration, location and the existence of the vents. The time history characteristics of the gas explosion overpressure, load distribution law, and explosion venting mechanism of vents in the trench were considered. The results showed that the overpressure–time history curve of the gas explosion in the trench with top vents has a single peak. The explosion overpressure initially increased and then decreased with increasing methane concentration, and the maximum overpressure was observed at a methane concentration of 9.5 vol%. The change rate in the overpressure–time history curve decreased upstream of each vent and increased downstream. In addition, the peak overpressure suddenly dropped upstream and jumped downstream of each vent. Adding vents to the top of the pipe trench significantly reduced the upstream overpressure and overall impulse, and the overpressure attenuated to a greater degree.